If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -4 = 4x + -5 Reorder the terms: -4 + 3x = 4x + -5 Reorder the terms: -4 + 3x = -5 + 4x Solving -4 + 3x = -5 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -4 + 3x + -4x = -5 + 4x + -4x Combine like terms: 3x + -4x = -1x -4 + -1x = -5 + 4x + -4x Combine like terms: 4x + -4x = 0 -4 + -1x = -5 + 0 -4 + -1x = -5 Add '4' to each side of the equation. -4 + 4 + -1x = -5 + 4 Combine like terms: -4 + 4 = 0 0 + -1x = -5 + 4 -1x = -5 + 4 Combine like terms: -5 + 4 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1
| x=3/5/1/4 | | 3.81=2x-2.31 | | x=3/5*1/4 | | -2x-3=-3x-3x+1 | | 3/10-1/6= | | 5x+3(x+6)=74 | | 2y^2-4y^3=0 | | .4(a+3)=2 | | -14-3x=16+2x | | 14=3s-4b | | x+5-5=17-5 | | log(6+x)+log(6-x)-logx=2 | | 4m^2+8m+32=0 | | 18-n/2 | | 11=3x-25 | | 10x+4x+3+6=8x+3+5x | | 12y^2+7y+10=0 | | 19x=23x+38 | | 500-11N=170 | | 3v/4=12 | | 2x+2x-14=x-9+x+2+x-7 | | -48x^5/6x | | 4.9t^2-10t+84=0 | | 5t+3=5(t+25)-22 | | (a+2)(a-5)(a+3)= | | 5t-4=44-t | | 3x^4/12x^2 | | -1/3y-4-7 | | Radx+5-radx-1=2 | | 9z+15=8z+12 | | Sinxcosy=7x^2 | | 5x+10=8x+10 |